The Alegories of the Other in (Post-)Modern Discourse - Žukauskaitė, Audronė (Sociologija. Mintis ir veiksmas, 1997)
The aim of the article is to discuss the meaning of the notion of the Other in the postmodern thought. The author suggests that before being defined as a programme the postmodern thought is a thought and a view of the Other, a view that connects the postmodern critique of society and culture with the works of Husserl, Heidegger, Levinas among others. The author builds her argument on the phenomenological critique of the subject-centered metaphysics of the New Age. In her interpretation of the phenomenological ideas of Levinas, Nancy and Heidegger the author suggests that the phenomenological recognition of the intersubjective grounds of subjectivity does not yet mean the recognition of the other in the social reality where the Other resides. On the basis of such interpretation the author argues that the interplay of immanence and transendence in the social reality is defining of the postmodern thought.